Proposed Social Media Marketing Strategy for Gaining Sales in New Normal Adaptation Era (The Indonesian Journal of Business Administration, 2021)
Hong Kong Boulevard is a sub-apparel brand inspired by Asian pop culture's past, present, and future. Bearing the motto ""Prescription for Boredom"" this unisex sub-apparel label reimagined various disciplines from Asian city pop music albums, 90s movies to retro-futuristic aesthetic comes with pop yet vibrant color for youth culture. Currently, COVID-19 causes economic contraction globally, and Hong Kong Boulevard needs to sustain from this issue and spread their presences to abundant people in Indonesia's digital market with a social media strategy regarding their declining sales trend due the COVID-19 began to affect the business. Current company goals are growing awareness in digital platforms and gaining sales through social media marketing on Instagram as their platform introduces to a broad market and sells their products due to maximizing positive sentiments in digital channels. This research aims to identify which of the marketing strategies or activities that can be used by Hong Kong Boulevard in order to gain its sales. The marketing activities could help Hong Kong Boulevard to improve its brand awareness, especially in this digital era where Instagram could give benefits in the digital era and the new normal adaptation era. In this research, the author will use internal and external analysis of the company using SWOT matrix, STP analysis, marketing mix, consumer-based brand equity, customer analysis, competitor analysis, and Porter Five Forces analysis. In order to do some of the analysis, the author uses the in-depth interview to gain insights about customer’s perception and motivation in term of purchase fashion product in new normal adaptation era. After doing some of the research stated before, the author found that there are gaps that Hong Kong Boulevard has especially in terms of marketing. some of the proposed activities for Hong Kong Boulevard are integrated marketing communication focusing on Instagram and provide e-commerce channels for consumers purchase options. These activities will manage in order to achieve targets. Keywords: fashion, marketing strategy, social media, new normal adaptation, COVID-19